Cytotoxic compounds from kibatalia gitingensis (Elm.) woodson - De Los Reyes, Mariquit M. (Animo Repository, 2017)
© 2016 Phcog.Net. Ursolic acid (1), squalene (2), a mixture of α-amyrin acetate (3a) and lupeol acetate (3b), and isoscopoletin (4), isolated from the dichloromethane extracts of the leaves and twigs of Kibatalia gitingensis, were evaluated for their cytotoxic activities against three human cancer cell lines, breast (MCF-7) and colon (HT-29 and HCT-116), and a normal cell line, human dermal fibroblast-neonatal (HDFn), using the in vitro PrestoBlue® cell viability assay. Compounds 1-4 exhibited strong cytotoxic activities against HT-29 cells with IC50 values ranging from 0.6931 to 1.083 μg/mL. Furthermore, 1-4 were moderately cytotoxic against HCT-116 cells with IC50 values ranging from 4.065 to 11.09 μg/mL. These compounds were least cytotoxic against MCF-7 cells with IC50 values ranging from 8.642 to 25.87 μg/mL. The most cytotoxic against HT-29 cells, HCT-116 cells and MCF-7 cells are 2, 4 and 1, respectively.